How does multiple sclerosis affect sexual satisfaction in patients' spouses? - Sedighi, Behnaz; Abedini Parizi, Maryam; Haghdoost, Ali Akbar; Jangipour Afshar, Parya; Shoraka, Hamid Reza; Jafari, Simin (Frontiers in Psychology, 2023)
Background: Sexual dysfunction (SD) is a common complaint among Multiple sclerosis (MS) patients with a significant impact on the quality of life (QoL) of afflicted couples. The purpose of this study was to determine sexual satisfaction (SS) in the spouses of MS patients and its impact on the QoL and also their correlation. Methods: 214 spouses of MS patients were enrolled in this cross-sectional study. They completed Larson sexual satisfaction questionnaire and SF-8 health survey. Results: The mean±SD age of spouses was 39.8±9.7 years, and the duration of MS was 5 years or less in most of their partners. The mean±SD score of QoL was 71.0±20.3 (out of 100), and the mean SS score was 89.2±18.6 (out of 125) which is categorized as moderate satisfaction; the highest score was among male spouses younger than 40 years old, also the SS was lower among female spouses. In the final model, we found that SD, psychiatric symptoms, cognitive impairment, and the level of disability of patients were independent explanatory factors for the SS of their spouses. Conclusion: As we may expect, our findings support the role of SS in the QoL of spouses of patients with MS; therefore, physicians’ attention to this hidden aspect of MS patients’ life is crucial.